(untitled) - IRRI (Los Banos, Philippines, 1983)
This book provides useful information on the consequences of mechanization of small farms in Southeast Asia which effects all production stages from lamd preparation through crop production, harvesting, and posharvest processing. Such changes are likely to have an impact on employment, income and income distribution, and social welfare. Evaluation of the consequences of machanization as well as formulation of appropriate policy guidelines is a predominantly empirical issue strongly related to local socioeconomic conditions
Keywords: agriculture - economic aspects,farm mechanization